UNCONTROL ON RUBEN ÖSTLUND’S FORCE MAJEURE - Johansson, Anders E. (The Nordic Journal of Aesthetics, 2018)
Ruben Östlund’s film Force Majeure (2014) was mostly received as a depiction of the crisis of masculinity. And it is, but that particular theme is also placed within a larger context concerning questions of value, understanding, order, and control, questions asked not only on a thematic level but also through cutting, framing, and the use of camera views. Not accepting any simple dichotomy between form and meaning, Force Majeure places itself firmly in an avant- garde and modernist tradition. Thereby the film is also related to this tradition’s ambition of investigating Western thought, knowledge and art anew, problematising given forms of rational thinking in order for something new to emerge. In the wake of World War II it was, for thinkers like Adorno, Foucault, Stockhausen, and Boulez, seen as unavoidable and urgent to deconstruct the conventions and norms that had made Auschwitz possible. It is still urgent. This article takes its starting point in the connections between avant-garde serialism in music, Foucault’s serialist methods of research and Deleuze’s theories of modernist film, in order to grasp how the aesthetics of Force Majeure continues to deconstruct.